Analisis Keuntungan Usaha Daging Kelapa Putih (White Meat) Studi Kasus Pada Usaha Bapak “F” di Desa Tontalete Kecamatan Kema Kabupaten Minahasa Utara - Punuh, Fidea Evalien Ester; Timban, Jean Fanny Junita; Maweikere, Audrey Julia Maria (Jurusan Sosial Ekonomi Pertanian, Fakultas Pertanian Universitas Sam Ratulangi, Manado, 2025)
This study aims to calculate and analyze the profits of the white meat business run by Mr. “F” in Tontalete Village, Kema District, North Minahasa Regency. This business uses white meat as its main product and coconut shells and husks as by-products. The main challenges faced include the absence of proper financial record-keeping and management, fluctuations in raw material prices, and labor costs and unforeseen expenses that may affect the smooth operation of the business. The research method employed is a case study with data collection conducted in March 2025. The data collected includes primary data obtained through interviews and secondary data from various literature and relevant institutions. The analysis used was a profit analysis and Revenue Cost Ratio (R/C Ratio) to assess the feasibility of the business. The research results showed that the total revenue of the business in March 2025 reached Rp718,644,760, with total costs of Rp597,410,026, resulting in a profit of Rp121,234,734. The R/C Ratio value of 1.2 indicates that every Rp1.0 spent generates Rp1.2 in revenue. Therefore, it can be concluded that the white coconut meat business operated by Mr. “F” is viable and worth developing as it can generate significant profits. However, better cost management and systematic financial record-keeping are necessary to ensure the business continues to grow and contribute to job creation for the local community.